Application of Centrifugation in the Escalation of the Production Process of Soy Drink in Nilo, Colombia - Malagón Sánchez, Carlos Alberto
The soy drink obtained in the production unit of the municipality of Nil, is used as raw material for the production of products consumed in food security programs, school canteens and senior citizens; The useful life of this beverage is short due to the presence of dough (Okara), this happens because the filtration operation, is done in a handcrafted way and does not allow to separate the solids properly, which affects the organoleptic characteristics, quality and safety Of the final product. The objective of this work was to apply and validate the centrifugation in the process of separation of the beverage mixture and soya (Okara), validated the efficiency of the process by comparing the drinks obtained in the different tests, it was verified that the Centrifugation allows to efficiently separate the beverage from the dough (Okara) in the process of soybean transformation.This initiative is aimed at carrying out a social work in which the Sena de Girardot, through the development of productive alternatives that improve working conditions and quality in the Nilo Productive Unit.